Urban Ecology of Arboviral Mosquito Vectors Along the Kenyan Coast. Issue 1 (5th July 2020) - Karisa, Jonathan; Muriu, Simon; Omuoyo, Donwilliams; Karia, Boniface; Ngari, Moses; Nyamwaya, Doris; Rono, Martin; Warimwe, George; Mwangangi, Joseph; Mbogo, Charles M
Abstract: The purpose of this study was to determine the ecology of the common arboviral mosquito vectors in Mombasa, Kilifi and Malindi urban areas of coastal Kenya. Mosquito larvae were collected using standard dippers and pipettes. Egg survivorship in dry soil was evaluated by collecting soil samples from dry potential larval developmental sites, re-hydrating them for hatching and rearing of the eventual larvae to adults. Adult mosquitoes were collected with CDC light traps and BG-Sentinel traps. All blood-fed females were tested for bloodmeal origin. Mosquitoes were screened for arboviruses using RT-qPCR. Overall, the predominant species were Culex quinquefasciatus (Say) 72.4% ( n = 2, 364) and Aedes aegypti (L.), 25.7%, ( n = 838). A total of 415 larval developmental sites were identified indoors ( n = 317) and outdoors ( n = 98). The most productive larval developmental sites, both indoors and outdoors, were assorted small containers, water tanks, drainages, drums, and jerricans. Overall, 62% ( n = 18) of the soil samples collected were positive for larvae which were used as a proxy to measure the presence of eggs. The mosquitoes fed on humans (29.8%) and chickens (3.7%). Of 259 mosquitoes tested for viral infection, 11.6% were positive for Flavivirus only. The most productive larval developmental sites for arboviral vectors indoors were small containers, water tanks, jerricans, and drums whereas small containers, water tanks, drainage channels, buckets, tires, and water troughs were the productive larval developmental sites outdoors.